Green synthesis of Au coated on ZnO nanoparticles using orange peel extract and its application for electrochemical detection of formaldehyde - Wicaksono, Wiyogo Prio; Dinnia, Nabilla; Yanti, Ika; Purwiandono, Gani; Fadillah, Ganjar (Journal of Research and Development on Nanotechnology, 2022)
We report the facile preparation of Au coated ZnO nanoparticles via a two-step green synthesis route. The aqueous of orange peel extract (OPE) was used both as biocomplexing and bioreducing agents, while the Zn(NO3)2 and HAuCl4 were employed as precursors. Initially, OPE was prepared to synthesize the ZnONPs, followed by the reduction of HAuCl4, generating Au coated on ZnO nanoparticles (Au/ZnONPs). The IR spectra at around 438.95 cm-1 confirmed the presence of Zn-O absorption in the nanoparticles, while it was not observed in the OPE. Further characterization using XRD and SEM-EDX indicated that the spherical of Au was successfully coated on the sponge-like structure of ZnO with the crystalline size of ZnONPs and Au/ZnONPs were 21.30 and 26.67 nm, respectively. The modified Au/ZnONPs on graphite paste electrode showed the excellent electrochemical detection of formaldehyde solution by the linearity range from 1 to 100 mM (R2=0.9945) with LOD of 10.27 mM and RSD of 0.39%. In addition, the modified electrode showed high selectivity toward formaldehyde, instead of ethanol.